The Effect of Health Facility and Ease of Accessibility on Satisfaction of BPJS PBPU Participant - Anggi Sepfana Zizilia; Bagus Setyoboedi; Rachmat Hargono; Kuntoro Kuntoro; Irwanto Irwanto; Nur Mukarromah (Health Notions, 2018)
BPJS is one of the Indonesian government, which maintains the social health insurance and is expected to guarantee the public health quality in Indonesia. This research was conducted to analyze the effect of the health facility and easier accessibility through the BPJS PBPU participant satisfaction. This research used observation method through cross sectional approach. The sampling method in this research was taken under the purposive sampling method with 245 respondents. The sample data was analyzed using the Chi Square statistical analysis to observe the effect of health facility offered and the easier accessibility given through the public satisfactory, who had been listed as BPJS participants. The result showed that the health facility did not give a significant difference with the p value of 0.197, while easier access was significantly different with the p value 0.000 < 0.005 through the BPJS PBPU participant satisfaction. The conclusion of this research was easier access had a significant effect through the BPJS PBPU satisfaction. It is also suggested to the government and BPJS Health Care for disuccsing further about the program along with the policy, as well as the quality service to increase the BPJS participant satisfaction, especially the BPJS PBPU satisfaction. Keywords: BPJS, PBPU, Health facility, Ease of Accessibility, Satisfaction